Evaluation of Government Policy in Governance of Educational Cooperation - Maryasih, Ni Luh Kerti; Soemartono, Triyuni; Effendi, Khasan; Rahmatsyah, T.Herry (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Special sports schools in Jakarta play an important role in producing outstanding athletes. However, the success of this program relies heavily on effective collaborative governance between the government, schools, and other stakeholders. This research will examine how government policies have supported the creation of optimal collaborative governance in the context of sports education in Jakarta. The study method used in this study uses a field method with a qualitative approach. The subjects in this study are the Head of the Curriculum Center, the Head of the DKI Jakarta Curriculum Sub-Directorate, the Principal, the Head of Curriculum, the Counseling Teacher, and representatives of parents and students of SMA Ragunan Sekolah Khusus Olahragawan Jakarta. The theory used in this research is William Dunn's Policy Evaluation theory, which uses data collection techniques using structured interviews, observation, and documentation. The study results can conclude that government policy in the governance of educational collaboration at the Jakarta Special School for Athletes has been running even though it has not been maximized. It is proposed that a curriculum policy that is more based on the conditions of special sports students be made so that the curriculum can be accepted and implemented optimally.